CLINICAL STUDY OF THE HYPOTHESIS OF ENDOGENOUS COLLATERAL WIND ON ACUTE CORONARY SYNDROME - Wang, Xian; Zhang, Cong; Yang, Ran; Zhu, Haiyan; Zhao, Huaibing; Li, Xiaoming (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Acute Coronary Syndrome (ACS), is a serious threat to people's health, and life, and in recent years, the incidence has increased yearly. This study was to propose the hypothesis of “endogenous collateral wind” based on the patho-mechanism of thrombogenesis complicated by ruptured plaque on ACS, and the theory of traditional Chinese medicine.Materials and Methods: Through successful coronary angiography (CAG), and intravascular ultrasound (IVUS),patients with coronary artery disease were made the differential diagnosis such as blood stasis, blood stasis due to phlegm obstruction, and endogenous collateral wind. The levels of plasma inflammatory marker were measured to study on the characteristics of “endogenous collateral wind”. Luo heng dripping pills with promoting blood circulation to expel wind-evil, and remove wetness were made based on the hypothesis of “endogenous collateral wind” on ACS. Patients with unstable angina were randomly divided into 3, groups based on therapeutic methods: conventional therapy group, Luo Heng dripping pills group and Tongxinluo caps. Differences among groups were compared. Results: There were great changes in number and degree of coronary arteriostenosis confirmed by CAG, the types of ACC/AHA lesion and Levin lesion confirmed by CAG, remodeling index, positive or negative remodeling percentage measured by IVUS, the plasma levels of plasma inflammatory marker measured by ELLSA in the patients with endogenous collateral wind, compared with patients with blood stasis and blood stasis due to phlegm obstruction. The total effective rate of improved angina in Luo Heng dripping pills group was significantly higher than those in other two groups. The levels of plasma inflammatory marker were significantly lower in Luo Heng dripping pills group.Conclusion: There were some pathological basis which were found about the hypothesis of “endogenous collateral wind” on acute coronary syndrome. It provided evidences for patients with coronary artery disease treated by medicines with expelling evil-wind, and removing wetness.